PENGARUH NON PERFORMING LOAN (NPL) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSET (ROA) PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siregar, Randi; Sembiring, Sabeth (Jurnal Manajemen dan Bisnis, 2020)
The purpose of this research was conducted to know the influence of: (1) Simultaneous Non Performing Loan and Loan to Deposit Ratio against Return On Asset, (2) Partial Non-Performing Loan against Return On Asset and (3) partial Loan to Deposit against Return On Asset Corporate Banking the Go Public period 2010 – 2012.The research uses quantitative research plans. The research subject is a banking company that go public from 2014 – 2016 and the objects are Non Performing Loan, Loan to Deposit Ratio and Return On Asset.Data collected using documentation methods and analyzed with multiple linear regression analyses. The results showed that (1) Non Performing Loan and Loan to Deposit Ratio simultaneously had significant effect on Return On Asset.(2) Non Performing Loan partially negative effect on Return On Asset, (3) Loan to Deposit Ratio positively affects the Return On Asset of the banking company listed on the Indonesia Stock Exchange.The value of the coefficient of determination (adjusted R2) of 0.323 or 32.3%, this translates to 32.3% of ROA variations that can be explained by variations of independent variables of the NPL and LDR.The remaining 67.7% is explained by other reasons outside of the regression model.Based on the results of multiple linear regression analyses indicating that the NPL has a significant negative impact on ROA, LDR has a significant and positive effect on Roa, NPL and LDR.